Feasibility and safety of day-surgery laparoscopic cholecystectomy: a single-institution 5-year experience of 1140 cases - Al-Omani, Saud (Korean J Hepatobiliary Pancreat Surg, 2015)
BACKGROUNDS/AIMS: We report our experience with day-surgery laparoscopic cholecystectomy and assess its feasibility and safety. METHODS: Data was collected on all the patients who underwent day-surgery laparoscopic cholecystectomy between February 2009 and February 2014 at Prince Sultan Military Medical City, Riyadh, Kingdom of Saudi Arabia. All patients had symptomatic cholelithiasis that was proven on imaging studies with clearance of the common bile duct. The patient biographical data (age, gender, American Society of Anaesthesiology status, medical comorbidities) and surgical outcomes were then obtained. There was an evaluation of the success rate of day-surgery laparoscopic cholecystectomy, reasons for unexpected admission, and the re-admission rate. RESULTS: A total of 1,140 patients were included in this study. The success rate for day-surgery laparoscopic cholecystectomy was 96%. The reasons for unexpected hospital admission for 46 patients (4%) included persistent abdominal pain and postoperative emesis. The postoperative re-admission rate was 0.4% (5 patients). There were no major complications, and the conversion rate was 0.5% (6 patients). CONCLUSIONS: We suggest that day-surgery laparoscopic cholecystectomy is both safe and feasible in a local setting. Careful patient selection is essential in ensuring a high success rate.